Influences of Calligraphy Education in Shenjiaying Primary School - Liu, Yan (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Calligraphy holds an important place in the life of Chinese people. Being a supreme form of art that keeps the Chinese culture, calligraphy is taught to young students. This study explores the impact of calligraphy education on the cognitive abilities, fine motor skills, and psychosocial skills of students in Shenjiaying Primary School. The study aims to evaluate the improvement effect of calligraphy education on students' memory, attention, hand-eye coordination, self-discipline, and cultural appreciation ability. This study employed purposive sampling, selecting three teachers, three students, and three parents from Shenjiaying Primary School in Huangshi City, Hubei Province as interview subjects under an exploratory case study design. A sample size of three participants per group ensures in-depth interviews, allowing for detailed collection of each participant's specific perceptions and feedback on calligraphy education. This approach avoids superficial information from large samples while meeting qualitative research requirements for "information saturation. Through thematic analysis, responses were collated then analyzed. The results indicate that calligraphy education significantly improves students' observation ability, memory, and hand-eye coordination, while enhancing their self-discipline and cultural identity. Based on these findings, a learning plan is proposed which aims at integrating calligraphy education more effectively into primary school curriculum to promote students' all-round development. The conclusion points out that calligraphy education is not only a cultivation of artistic skills, but also an important way to enhance students' cognitive and psychological qualities. Calligraphy education can be effectively integrated into primary school classrooms through grade-segmented teaching, interdisciplinary linkages, and home-school collaboration.